Analysis and design of veneer cover soils. Issue 1 (1st January 2005) - Koerner, R. M.; Soong, T.-Y.
Abstract : Cover soil sliding on slopes underlain by geosynthetics is obviously an unacceptable situation and, if the number of occurrences becomes excessive, can eventually reflect poorly on the entire technology. Steeply sloped leachate collection layers and final covers of landfills are situations where incidents of such sliding have occurred. Paradoxically, the analytic formulation of the situation is quite straightforward. This paper presents an analysis of the common problem of a veneer of cover soil (0.3 to 1.0 m thick) on a geosynthetic material at a given slope angle and length. The paper then presents different scenarios that create lower FS (factor of safety) -values than the gravitational stresses of the above situation, e.g. equipment loads, seepage forces and seismic loads. As a counterpoint, different scenarios that create higher FS-values also are presented, e.g. toe berms, tapered thicknesses and veneer reinforcement. In this latter category, a subdivision is made into intentional reinforcement (using geogrids or high-strength geotextiles) and non-intentional reinforcement (cases where geosynthetics overlay a weak interface within a multilined slope). A standard numeric example is used in each of the above situations to illustrate the various influences on the resulting FS-value. In many cases, design curves are also formulated. Suggested minimum FS-values are presented for final closures of landfills, waste piles, leach pads, etc., which are the situations where veneer slides of this type are the most serious. Hopefully, the paper will serve as a vehicle to bring a greater awareness to this situation so as to avert such slides from occurring in the future. Note: This paper was initially published as the Giroud Lecture in the Proceedings of the Sixth International Geosynthetics Conference held in Atlanta, USA, in 1998.